Monetary policy news and exchange rate responses: Do only surprises matter? - Fatum, Rasmus; Scholnick, Barry (Journal of Banking & Finance, 2008)
We use data from the Federal Funds Futures market to show that exchange rates respond to only the surprise component of an actual US monetary policy change and we illustrate that failure to disentangle the surprise component from the actual monetary policy change can lead to an underestimation of the impact of monetary policy, or even to a false rejection of the hypothesis that monetary policy impacts exchange rates. Unlike the recent contributions to the literature on exchange rates and monetary policy news, our testing method avoids the imposition of assumptions regarding exchange rate market efficiency. We also add to the debate on how quickly exchange rates respond to news by showing that the exchange rates under study absorb monetary policy surprises within the same day as the news are announced.